Problems with estimation and interpretation of oceanic heat transport – conceptual remarks for the case of Fram Strait in the Arctic Ocean - U. Schauer; A. Beszczynska-Möller (Ocean Science, 2009)
While the concept of oceanic heat transport – or rather heat transport divergence – is well known, it is sometimes applied inaccurately. Often so-called "heat transports" are computed across a partial section which means that the volume flow through such a section is not zero. In this case the "heat transports" depend entirely on the choice of the temperature scale. The consequences of such arbitrariness are demonstrated with a simple calculation exercise for the passages to the Arctic Ocean. To circumvent the arising difficulties for the Fram Strait in the Arctic we propose a stream tube concept to define a net zero volume flow section which can, with coarse assumptions, be used to determine oceanic heat transport by the portion of Atlantic water flow that passes through Fram Strait. Weaknesses of this approach and consequences for observational strategies are discussed.